Respuesta :

Answer:

sorry i don't know

Step-by-step explanation:

but i can help you with anything else

just give me a message and i will be straight with you

Answer:

9

Step-by-step explanation:

Using the rules of exponents/ radicals

[tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^{m} }[/tex]

[tex](^m)^{n}[/tex] = [tex]a^{mn}[/tex]

[tex]a^{\frac{m}{n} }[/tex] ⇔ [tex]\sqrt[n]{a^{m} }[/tex]

Thus

[tex](\frac{1}{27}) ^{\frac{1}{3} }[/tex] = [tex]\frac{1}{27^{\frac{1}{3} } }[/tex] = [tex]\frac{1}{\sqrt[3]{27} }[/tex] = [tex]\frac{1}{3}[/tex]

[tex](\frac{1}{81}) ^{-\frac{3}{4} }[/tex]

= [tex]\frac{1}{81^{-\frac{3}{4} } }[/tex]

= [tex]81^{\frac{3}{4} }[/tex]

= [tex](\sqrt[4]{81} )^3[/tex] = 3³ = 27

Thus

[tex]\frac{1}{3}[/tex] × 27 = 9